2018
DOI: 10.21831/cp.v37i2.16491
|View full text |Cite
|
Sign up to set email alerts
|

Developing Four Tier Misconception Diagnostic Test About Kinematics

Abstract: Abstrak: Penelitian ini bertujuan untuk mengembangkan instrumen Tes Diagnostik Miskonsepsi Empat Tahap Tentang Kinematika (TDMET-K) yang dapat mendeskripsikan profil miskonsepsi guru fisika SMA dengan kriteria baik. Penelitian menggunakan metode penelitian & pengembangan dengan guru fisika SMA di Surakarta sebagai subjek penelitian. Tahapan penelitian terdiri atas kajian literatur untuk menyusun draf awal; uji validitas secara kualitatif oleh dua ahli; uji validitas isi secara kuantitatif menggunakan formula L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Instruments that have been developed by indicators of mathematical representation ability and item descriptions (Appendix 1) will be validated (content validity) through expert judgment using the instrument item review criteria (Appendix 2) (Pujayanto et al 2018). The content validity of the test instrument is obtained by providing the test instrument developed to the experts for review.…”
Section: Data Collection Mathematical Representation Ability Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Instruments that have been developed by indicators of mathematical representation ability and item descriptions (Appendix 1) will be validated (content validity) through expert judgment using the instrument item review criteria (Appendix 2) (Pujayanto et al 2018). The content validity of the test instrument is obtained by providing the test instrument developed to the experts for review.…”
Section: Data Collection Mathematical Representation Ability Testmentioning
confidence: 99%
“…The application of diagnostic assessments in learning will be the teacher's reference to ensure teacher achievement and progress in explaining the material that has been taught (Nitko & Brookhart, 2011;Pujayanto et al 2018). Facts on the field show that there are still many teachers who do not understand the diagnostic assessment instrument model (Pujayanto et al 2018). Based on observations at several high schools in the Special Region of Yogyakarta, diagnostic assessments are seldom carried out in the learning process because standardized test instruments to measure ability and detect student difficulties are not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Student's misconception in this study was identified using four-tier diagnostic test. The development of diagnostic test forms from one-tier become two-tier, three-tier, and four-tier based on several considerations, for instance the certainty of the students' answer and the students' confidence in choosing the answers and explaining the reasons (Pujayanto, 2018).…”
Section: Figure 1 Percentage Of Student's Conception On the Topic Of Populationmentioning
confidence: 99%
“…The four-tier multilevel multiple-choice test is free of error and misunderstanding diagnostic test, which is very practical and useful for diagnosing misconceptions. The effectiveness of the four-tier has succeeded in identifying misconceptions in various concepts such as fluid (Dewi et al, 2019), vibration and waves (Negoro & Karina, 2019), kinematics (Pujayanto, 2018), and heart and blood vessels (Syarafina et al, 2020). Exploring misconceptions that students may experience is important to develop how learning will be given to students.…”
Section: Introductionmentioning
confidence: 99%